2007
DOI: 10.1200/jco.2006.07.0482
|View full text |Cite
|
Sign up to set email alerts
|

Two Cycles of Doxorubicin, Bleomycin, Vinblastine, and Dacarbazine Plus Extended-Field Radiotherapy Is Superior to Radiotherapy Alone in Early Favorable Hodgkin's Lymphoma: Final Results of the GHSG HD7 Trial

Abstract: CMT consisting of two cycles of ABVD plus EF-RT is more effective than EF-RT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(101 citation statements)
references
References 34 publications
1
95
0
5
Order By: Relevance
“…Three groups have reported the results based on the use of brief exposure to ABVD followed by irradiation for clinical stage IA or IIA non-bulky HL [47], [48] and [49]. The results from these studies favour this approach in minimising the risks for later infertility, premature menopause, leukaemia as well as cardiopulmonary toxicity [50] and [51].…”
Section: Limitedmentioning
confidence: 99%
“…Three groups have reported the results based on the use of brief exposure to ABVD followed by irradiation for clinical stage IA or IIA non-bulky HL [47], [48] and [49]. The results from these studies favour this approach in minimising the risks for later infertility, premature menopause, leukaemia as well as cardiopulmonary toxicity [50] and [51].…”
Section: Limitedmentioning
confidence: 99%
“…Later trials revealed that the risk of relapse in non-irradiated sites was approximately 20-30% and that a number of these relapsed patients were rescued by chemotherapy (CT). This warranted investigation to determine whether combined modality therapy (CT + RT) improves the results as compared to RT alone (8)(9)(10)(11)(12). A number of trials have assessed the possibility of treating HL patients with CT alone (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In the GHSG HD7 trial, patients were randomly assigned to receive either 30 Gy extended-field RT (EF-RT) alone or two cycles of ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) followed by the same RT [2]. Response rates did not differ between treatment arms.…”
Section: Treatment Of Early Favorable Hlmentioning
confidence: 99%